Composite SERS-based satellites navigated by optical tweezers for single cell analysis1. Issue 15 (7th August 2015) - Stetciura, Inna Y.; Yashchenok, Alexey; Masic, Admir; Lyubin, Evgeny V.; Inozemtseva, Olga A.; Drozdova, Maria G.; Markvichova, Elena A.; Khlebtsov, Boris N.; Fedyanin, Andrey A.; Sukhorukov, Gleb B.; Gorin, Dmitry A.; Volodkin, Dmitry
<x xml:space="preserve">Abstract</x> Optically movable SERS micro-satellites are effective intracellular probes.